Early RSV infection aggravates asthma-related Th2 responses by increasing the number of CD4+ TRM cells through upregulation of PLZF - Zhang Meng; Sha Jiafeng; Li Na; Feng Jingjing; Shi Tianyun; Yu Yunxia; Ren Xiaoting; Mei Zhoufang; Jie Zhijun (Acta Biochimica et Biophysica Sinica)
Respiratory syncytial virus (RSV) infection is correlated with the chronic pathogenesis and exacerbation of asthma. However, the mechanism remains unclear. In this study, acute and memory (Mem) asthma models with early RSV infection are established to explore the persistence of the effects of RSV infection on asthma. Intravascular injection of an anti-CD45 antibody is performed to define CD4+ TRM cells accurately. RSV infection has a sustained impact on asthma exacerbation for at least six weeks, with high Th2 cytokine secretion in lung tissue instead of IgE response-related B cells. CD45–CD4+ TRM cells are positively correlated with RSV-related asthma exacerbation and severe airway inflammation. Mechanistically, overexpression of the transcription factor PLZF in vitro increases the number of CD4+ TRM cells, and conditional knockout of Zbtb16 (encoding PLZF) can decrease the number of CD4+ TRM cells to aggravate allergic inflammation and reduce Th2 responses. This study provides evidence for potential combined strategies that might benefit asthma patients.